البيع بالتقسيط - دراسة فقهية مقارنة - - مسعي عون, الحسين; عياشي عمر, بشير; بن بردي, يوسف (University of Eloued-جامعة الوادي, 2015)
تناول هذا البحث دراسة فقهية مقارنة التي فيها خلاف بين الائمة الأربعة واقتصرناه على البيع بالتقسيط وقد اشتملت خطة هذه الرسالة على مقدمة وثلاث مباحث وخاتمة. في المبحث الأول: فأما المبحث الأول فقد اشتمل على بيان ماهية البيع بالتقسيط وقد تم تقسيم هذا المبحث الى مطلبين: مطلب الأول تضمن تعريف البيع بالتقسيط والمطلب الثاني تضمن مشروعيته وحكمه من مشروعيته أما في المبحث الثاني: تناول ثلاث مطالب في المطلب الأول تناول الضوابط الشرعية أما في المطلب الثاني: فتناولنا آدابه الشرعية أما المطلب الثالث: فتناولنا أيضا صوره المعاصرة أما في المبحث الثالث: فتناولنا البيع بالتقسيط عند الفقهاء وبضبط في حكم الزيارة في الثمن، وكان المبحث متفرع الى ثلاثة مطالب المطلب الأول: فتناولنا آراء المجيزون وادلتهم كذلك أما المطلب الثالث: فكان مستعرض لام المناقشات والردود الفريقين وتناول كذلك الراي من كلا الفريقين. أما الخاتمة: فأوردنا أهم النتائج التي توصلنا اليها من خلال هذا البحث )البيع بالتقسيط( والتي من أهمها: أنه لما كان البيع بالتقسيط يتضمن اختيار المشتري برضاه وارادته للثمن الاجل مع الزيادة قبل التفرق من المجلس، وبناء على ما أقامه الجمهور من ادلة قوية تنفي التشابه بين الزيادة في الثمن عند البيع بالتقسيط وبين الزيادة في الربا كل هذا كان مرجحا ومعززا للقول بصحة التعامل ببيع بالتقسيط، وانه لا إثم ولا حرمة فيه ولا شية. Summary This research doctrinal comparative study in which the dispute between the four imams and Aguetsrnah on installment sales have included this message plan on the front and three sections and a conclusion. In the first section: As for the first part, it has included a statement of what the installment sale has been this section is divided into two demands: I demand to ensure the definition of installment sales and second requirement ensures legitimacy and legitimacy of his rule In the second section the three demands of the first demand eating Shariah In the second requirement: Vtnolna etiquette legitimacy The third demand: Also Vtnolna contemporary image In the third section: Vtnolna installment sales when scholars and adjusts in the rule of the visit in the price, and was a topic Off to three demands First requirement: Vtnolna Almgizon views and their evidence as well The third requirement: L browser was discussions and responses of both teams and eat as well as the view from both teams. The conclusion: Voordna the most important results of the T we reached through this research (installment sale) and the most important of which: That, since the installment sale includes the buyer's choice with his consent and his will for the eighth term with the increase before separating from the board, and based on what set up by the public of strong evidence denies similarities between the increase in the price when installment sales and the increase in the usury All this was likely and enhanced to argue the validity of deal to sell in installments , and he did not sin or not the sanctity Shih
مذكرة ليسانس
Keywords: البيع/التقسيط /دراسة فقهية; Vente/versement/étude jurisprudentielle